The Effect of Physicians' Characteristics on Adoption of Electronic Health Care ‎Records ‎Based on the Technology Acceptance Model in Hospitals of Tehran ‎University of Medical ‎Sciences, Iran - Mohammadhiwa Abdekhoda; Maryam Ahmadi; Alireza Noruzi; Mohmoudreza Gohari (مدیریت اطلاعات سلامت, 2016)
Introduction: Physicians’ resistance to accepting and adopting Electronic Health Care Record (EHCR) ‎is still a serious challenge to the nationwide adoption of EHCR. As a result, ‎identification of the factors that contribute to this challenge is valuable. Thus, this study ‎was performed to survey the effect of physicians' characteristics on adoption of EHCR.